Peningkatan Keterampilan Membaca Pemahaman Teks Narasi Menggunakan Model Cooperative Tipe Teams Games Tournament di Kelas IV SDN 34 Jorong Dama Gadang Kabupaten Agam - Fadilla, Silvia; Desyandri, Desyandri (Lembaga Intelektual Muda Maluku, 2025)
This study aims to describe how the improvement of reading comprehension skills in narrative texts of students in Indonesian language learning using the Teams Games Tournament (TGT) model in the 4th grade of SDN 34 Jorong Dama Gadang, Agam Regency. The type of research is Classroom Action Research (CAR) using both qualitative and quantitative approaches. This research was conducted over two cycles, with research procedures consisting of planning, implementation, observation, and reflection. Data collection techniques included tests and non-tests. The subjects of this study are the classroom teacher as the observer, the researcher as the practitioner or teacher, and 17 students from the 4th grade of SDN 34 Jorong Dama Gadang. The research results show that the average score of the teaching module in cycle I was 83.3% (B), which increased to 95.8% (SB) in cycle II. The implementation of the teacher aspect in cycle I had an average score of 82.14% (B), which increased to 96.42% (SB) in cycle II. The implementation of the student aspect in cycle I had an average score of 83.92% (B), which increased to 96.42% (SB) in cycle II. The reading comprehension skills of the students in cycle I had an average score of 74% (C), which increased to 86.80% (B) in cycle II. Thus, it can be concluded that the TGT model can improve the reading comprehension skills of the students in narrative text during Bahasa Indonesia learning in grade IV at SDN 34 Jorong Dama Gadang, Agam District.